Pengaruh Bullying Terhadap Karakter Anak - Tita Suldianti; Manto (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to evaluate and illustrate the effect of bullying on children's character development. A quantitative approach was employed in this research. The population consisted of 256 students, with a sample of 27 respondents selected through purposive sampling from students at SD Negeri 25 Kota Pagar Alam. Data were collected using a questionnaire and analyzed with SPSS version 23 using the T-test method.The results indicated that bullying does not have a significant effect on children's character development, particularly regarding self-confidence. The significance value was 0.946, which exceeds the 0.05 threshold, indicating no significant influence of variable X (bullying) on variable Y (self-confidence). Furthermore, the coefficient of determination (R²) was -0.040, showing that only around 4% of the variation in students' self-confidence could be attributed to verbal bullying. This suggests a negligible or non-existent relationship between bullying and self-confidence.